Development of a rapid multiplex PCR assay for the detection of common pathogens associated with community-acquired pneumonia. (20th May 2021) - Koo, Seok Hwee; Jiang, Boran; Lim, Pei Qi; La, My-Van; Tan, Thean Yen
Abstract: Background: Community-acquired pneumonia (CAP) is one of the most common infectious diseases and is a significant cause of mortality and morbidity globally. A microbial cause was not determined in a sizable percentage of patients with CAP; there are increasing data to suggest regional differences in bacterial aetiology. We devised a multiplex real-time PCR assay for detecting four microorganisms ( Streptococcus pneumoniae, Haemophilus influenzae, Klebsiella pneumoniae and Burkholderia pseudomallei ) of relevance to CAP infections in Asia. Methods: Analytical validation was accomplished using bacterial isolates (n=10–33 of each target organism for analytical sensitivity and n=117 for analytical sensitivity) and clinical validation using 58 culture-positive respiratory tract specimens. Results: The qPCR assay exhibited 100% analytical sensitivity and analytical specificity, and 100% clinical sensitivity and 94–100% clinical specificity. The limit of detection and efficiency for the multiplex PCR assay were 3–33 CFU/mL and 93–110%, respectively. The results showed that the PCR-based method had higher sensitivity than traditional culture-based methods. The assay also demonstrated an ability to semiquantify bacterial loads. Conclusion: We have devised a reliable laboratory-developed multiplex qPCR assay, with a turnaround time of within one working day, for detection of four clinically important CAP-associated microorganisms in Asia. The availability of a test with improved diagnostic capabilities potentially leads to an informed choice of antibiotic usage and appropriate management of the patient to achieve a better treatment outcome and financial savings.